Analysis of the influencing factors of Chinese college students' investment and financial management - Feng, Lintao; Špecián, Petr; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
The bachelor thesis analyzes the factors that influence Chinese university students' investment and financial management behavior. Investment behavior is not only a means of making money, but also a manifestation of financial ability. Therefore, the author aims to analyze which factors affect college students' participation in investment, and which aspects hinder college students' participation in investment. The thesis draws on Chen and Volpe (1998) to examine the influence of gender, age and class rank. Furthermore, it adds factors of herd mentality, peer effects and risk preference. The author constructed a binary logistic model and used the stepwise regression method to analyze the significance and impact of the study factors in relation to college students' involvement in financial investment behavior. In the regression analysis, class rank, family, peer effects, financial knowledge and risk preference had a significant effect at the 0.1 level of significance on the likelihood of university students participation in financial investment behavior. With the increase in financial knowledge acquisition methods, the possibility of college students participating in investment and financial management will also increase. And compared with risk averse students, risk seeking students are more likely to participate in investment, while risk neutral students are lower than risk averse students.
Vedoucí práce: Petr Špecián
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses